Strategi Media Promosi Pada Destinasi Pariwisata Istana Pagaruyung - Komala Dewi, Ranti (Jurnal Ilmiah Pariwisata, 2012)
Pagaruyung palace is a famous tourist destination in West Sumatera, is located in Batusangkar, Tanah Datar. Pagaruyung palace is a building of high cultural value that reflects the culture of the Minangkabau. The palace is a replica of heritage Minangkabau royal that still exists from the 14th century. To promote development tourism in Pagaruyung Palace, the government has made rehabilitation, but on February 27, 2007 attacked by ugly fire once again caused by thunderbolt struck the top of palace’s roof. Therefore, tourism in Pagaruyung not develop optimally, it is necessary to boost local tourism activities in Pagaruyung to both local and foreign tourists to stay longer and get a different experience, and for pagaruyung peoples where tourism can create opportunities for business and for government can be a source of revenue. This study aims to examine how to increase tourist arrivals in the Pagaruyung Palace through promotion, and to find out how the concept of tourism promotion at Pagaruyung Palace, government and community participation in promoting tourism at Pagaruyung Palace, and formulate and also recommend the concept of proper media promotion strategy for tourism destination Pagaruyung Palace. The method used was distribute questionnaires to the Pagaruyung peoples, national tourists, and interviews on international tourists. The results or recommendations of research for promotion strategy concepts at Pagaruyung Palace are: (a) Pagaruyung peoples; increase promotion programs Pagaruyung Palace on local media, local newspapers and local radio, (b) national tourists; improve promotion through media such as local newspapers, national magazines, television, internet and travel brochures,  c) tourists; enhance the promotion through media television, internet and travel brochures.